Kepuasan Konsumen pada Manajemen Harga yang Ditetapkan oleh UMKM Ayam Geprek 71 Bandung di saat Lonjakan Harga Bahan Pokok di Indonesia - Janan, Nuhi Husnun; Fira, Endah Bellamia (International Journal Administration, Business & Organization, 2022)
Micro Small Medium Enterprises (MSMEs) are easily affected by every change. Thus, business people need to have a mature strategy in order to keep up with the changes. Ayam Geprek 71 MSME has a pretty good growth opportunity because it is located in a campus area with a clear target consumer. Consumers are one of the things that can affect the sustainability of a business. If the intended consumer's interest is not in accordance with the products offered, the strategy used needs to be re-evaluated. In addition, economic factors also greatly affect the price of basic commodities which affect the selling price of the product. The increase in the price of basic commodities such as cooking oil also affects the price increase offered by MSMEs Ayam Geprek 71. Even though the price offered by the MSME Ayam Geprek 71 has increased, it does not reduce consumer interest too much because it already has a value of trust in the MSME Ayam Geprek 71 product.